Saudi Students’ Attitudes toward Using Blackboard as the Medium of Education During the Pandemic - Albar, Hanan (International Journal of Linguistics and Translation Studies, 2023)
This study aimed to (1) investigate the overall effects of online education on TUELC students’ learning and (2) investigate the attitudes of TUELC students towards using Blackboard as a medium of education at all TU levels. The participants consisted of 121 male and female EFL students who took a questionnaire consisting of 19 items (9 items investigating the overall effects of online education on students’ learning and 10 items about the effects of online learning on TUELC students’ motivation). Students showed a high level of acceptance and support shown by students for Blackboard. Additionally, Blackboard was perceived to have mostly positive effects on their engagement in class but did not lead to an increase in interaction. Furthermore, the majority of the students agreed that Blackboard sessions were easier to participate in than traditional face-to-face sessions.